2019
DOI: 10.1002/msc.1383
|View full text |Cite
|
Sign up to set email alerts
|

How do UK physiotherapists address weight loss among individuals with hip osteoarthritis? A mixed‐methods study

Abstract: Background: Weight loss is recommended as a core treatment for individuals with hip osteoarthritis who are overweight or obese. Physiotherapists play an important role in managing patients with hip osteoarthritis, but little is known about how they address weight. We aimed to explore how UK-based physiotherapists currently address weight loss among individuals with hip OA.Methods: We carried out a mixed-methods study. A cross-sectional questionnaire was mailed to 3,126 UK-based musculoskeletal physiotherapists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…For instance, for patients with anxiety/depression who are beginning an exercise programme, signposting for additional mental health assessment, talking therapies and tailored medication may improve clinical outcomes. For those who are obese, signposting to additional lifestyle programmes and actively addressing weight loss as part of the exercise programme may also be of benefit, although how effectively this is addressed currently can be variable (Holden et al, ; Quicke, Holden, Bennell, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, for patients with anxiety/depression who are beginning an exercise programme, signposting for additional mental health assessment, talking therapies and tailored medication may improve clinical outcomes. For those who are obese, signposting to additional lifestyle programmes and actively addressing weight loss as part of the exercise programme may also be of benefit, although how effectively this is addressed currently can be variable (Holden et al, ; Quicke, Holden, Bennell, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, there are relatively few weight loss services in Norway that the GP can refer to, and the GPs may not be aware of those. In a previous study, a large proportion of PTs reported that they would address weight by the provision of advice, but some lacked confidence in addressing weight loss [33]. While PTs believe they have a role in addressing weight loss, they felt inadequately equipped to integrate weight loss in their management approach [56].…”
Section: Discussionmentioning
confidence: 99%
“…Also, observational studies have revealed low pass rates for weight management uncovering a large scope for improvement [31,51,[53][54][55]. The low pass rates may be related to health professionals' barriers towards discussing weight issues and their prioritizing to review other aspects of health [32,33,35]. Further, there are relatively few weight loss services in Norway that the GP can refer to, and the GPs may not be aware of those.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical therapists may be well placed to upskill to engage in basic caloric restriction guidance as part of integrated weight management practice for people with OA, given their skills in exercise prescription and health behavior change and the length of time spent with patients. However, research globally indicates that most physical therapists lack the knowledge and skills to integrate weight management into their treatment paradigm (17)(18)(19)(20). Australian physical therapists describe difficulty managing patients with comorbid obesity, and if they do provide education about weight loss, they predominantly advise about why weight loss is important rather than advise about how to lose weight (17,18,20,21).…”
Section: Introductionmentioning
confidence: 99%